2013
DOI: 10.1097/sla.0b013e3182a5021d
|View full text |Cite
|
Sign up to set email alerts
|

Improving Mortality Following Emergent Surgery in Older Patients Requires Focus on Complication Rescue

Abstract: Structured Abstract Objective To determine if a hospital’s ability to rescue patients from major complications underlies variation in outcomes for elderly patients undergoing emergency surgery. Summary Background Data Perioperative mortality rates in elderly patients undergoing emergent general/vascular operations are high and vary widely across Michigan hospitals. Methods We identified 23,224 patients undergoing emergent general/vascular surgery procedures at 41 hospitals within the Michigan Surgical Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 21 publications
(19 reference statements)
1
34
0
1
Order By: Relevance
“…Similar to other studies, we found that complications resulting from emergent surgeries can lead to worsened clinical status, additional hospital costs and, perhaps more importantly, decline in functional status requiring additional support or alternate level of care when leaving hospital. 10 A recent study by Sheetz and colleagues 11 reported a poor correlation between complications and mortality, but failure to rescue patients from in-hospital complications was significantly associated with mortality, and this association was greater in patients older than 75 years. In our study the most common complications were cardiac events, surgical infection/sepsis and postoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other studies, we found that complications resulting from emergent surgeries can lead to worsened clinical status, additional hospital costs and, perhaps more importantly, decline in functional status requiring additional support or alternate level of care when leaving hospital. 10 A recent study by Sheetz and colleagues 11 reported a poor correlation between complications and mortality, but failure to rescue patients from in-hospital complications was significantly associated with mortality, and this association was greater in patients older than 75 years. In our study the most common complications were cardiac events, surgical infection/sepsis and postoperative bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…1, 2 Though its mechanisms are incompletely understood, national and regional surgical quality collaboratives are providing hospitals with their own data on failure to rescue as a means of facilitating safer care practices. 3, 4 Reporting within these collaboratives or publicly through efforts such as the Centers for Medicare and Medicaid Services (CMS) Value Based Purchasing Program (VBP) have made hospitals' data on surgical safety more accessible to patient and policymaker scrutiny.…”
Section: Introductionmentioning
confidence: 99%
“…(35) In this context, recent evidence suggests that reducing failure to rescue events may be the most appropriate target for quality improvement within this demographic. (6)…”
Section: Introductionmentioning
confidence: 99%